The political economy of reforming agricultural support policies - Vos, Rob; Martin, Will; Resnick, Danielle (International Food Policy Research Institute, 2022)
Agricultural support policies cost more than US$800 billion per year in transfers to the farm sector worldwide. Support policies based on subsidies and trade barriers are highly distortive to markets and are also regressive as most support is provided to larger farmers. On balance, the incentives this support creates appear to increase greenhouse gas emissions that contribute to climate change. In addition, some subsidies undermine the production of more nutrient-dense commodities that are otherwise critical for the improvement of dietary outcomes. This paper first highlights that better outcomes could be achieved if even a small portion of agricultural subsidies were repurposed into investments in research and development (R&D) dedicated to productivity-enhancing and emission-reducing technologies. This would create multiple wins — mitigating global climate change, reducing poverty, increasing food security, and improving nutrition. Nonetheless, the political economy challenges to doing so are sizeable. Because current support policies are often politically popular and serve well-organized interests, reform is difficult without committed political leadership and multilateral collaboration. Using several case studies of both successful and failed changes of agricultural support policies in China, India, and the EU and the United States, we highlight lessons learned about the political economy constraints on and possibilities for reform.